2024
DOI: 10.3390/s24030761
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Zio XT Patch Accelerometer for the Objective Assessment of Physical Activity in the Atherosclerosis Risk in Communities (ARIC) Study

Anis Davoudi,
Jacek K. Urbanek,
Lacey Etzkorn
et al.

Abstract: Background: Combination devices to monitor heart rate/rhythms and physical activity are becoming increasingly popular in research and clinical settings. The Zio XT Patch (iRhythm Technologies, San Francisco, CA, USA) is US Food and Drug Administration (FDA)-approved for monitoring heart rhythms, but the validity of its accelerometer for assessing physical activity is unknown. Objective: To validate the accelerometer in the Zio XT Patch for measuring physical activity against the widely-used ActiGraph GT3X. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…We had previously shown that this measure of total amount of PA was highly correlated with total activity counts from the ActiGraph accelerometer. 5 Although the summary measures of HRV were not related to cognitive function in this study, it is possible that more detailed metrics of long-term HRV are associated with cognitive function. Specifically, it might be necessary to examine HRV by time-of-day.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…We had previously shown that this measure of total amount of PA was highly correlated with total activity counts from the ActiGraph accelerometer. 5 Although the summary measures of HRV were not related to cognitive function in this study, it is possible that more detailed metrics of long-term HRV are associated with cognitive function. Specifically, it might be necessary to examine HRV by time-of-day.…”
Section: Discussionmentioning
confidence: 64%
“…16 A recent study also validated MAD from the Zio ® XT Patch against total activity counts measured using the ActiGraph wrist accelerometer. 5 Second, minute-level MAD measurements were screened for periods of wear and non-wear based on the simultaneously measured ECG data. Third, days with more than 144 (10%) non-wear minutes were excluded, and participants with fewer than three valid days were excluded from further analysis.…”
Section: Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…MAD is strongly correlated with activity counts [18], heart rate [17], and PA intensity [17]. A recent study has also validated MAD from the Zio ® XT Patch against total activity counts measured using the ActiGraph wrist accelerometer [6]. Second, minute-level MAD measurements were screened for periods of wear and non-wear based on the simultaneously measured ECG data.…”
Section: Physical Activitymentioning
confidence: 99%
“…Yet, there are barriers to integrating these devices into clinical environments [5]. Recent work from our group found that accelerometry data measured by the Zio ® XT Patch, a commonly used ambulatory electrocardiogram (ECG) monitor capable of continuous (i.e., uninterrupted) wear for up to 14 days, was highly correlated with ActiGraph wrist accelerometry data [6]. To determine the potential utility of wearable ECG monitors with embedded accelerometers, it is important to evaluate associations between accelerometer-measured PA and important clinical outcomes, such as cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%